Nekotorye itogi issledovaniya problemy individualizatsii podgotovki yunykh sportsmenov - Nikitushkin, V. G.; Kvashuk, P. V. (Teorija i Praktika fiziceskoj Kul'tury, 1998)
The purpose of this paper was to substantiate the methods of young athletes training`s individualization. The authors consider that the functional-timing principle of the individual - typological indicators` systematization, taking into consideration the inherent and the created constitutional peculiarities of young athletes is the basic one to improve the system of their individual training`s control.